FOSTERING NATIONALISM THROUGH THE DEVELOPMENT OF A NATIONAL CAR PROTOTYPE: OPTIMIZING PROJECT-LEARNING INTERACTIVE FEATURES IN THE AUTOMOTIVE BODY ENGINEERING COURSE - Rudiyanto, Eddy; Mindarta, Erwin Komara; Sutadji, Eddy (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Indonesia’s struggle to establish a sustainable national automotive industry reflects deeper gaps in vocational education, particularly in embedding national identity within technical skill development. This study aims to design, implement, and evaluate a Project-Learning Interactive (PLI) model that integrates cultural and national narratives into the Automotive Body Engineering course, using the concept of a national car prototype as a contextual anchor. A mixed-methods research design was employed, combining pre- and post-intervention tests, reflective journals, observation, and expert validation. The PLI model was developed using the ADDIE framework and implemented over a semester with vocational students. Instruments were used to assess technical competence and technological nationalism, supported by qualitative thematic analysis. Results showed significant improvements in students’ vehicle design skills and affective engagement. Quantitatively, rubric-based performance scores increased, and nationalism-related attitudes strengthened. Qualitatively, students demonstrated heightened pride, cultural awareness, and collaborative innovation, as reflected in their design outputs featuring national motifs. The study identified five thematic indicators of technological nationalism, highlighting students’ alignment with national development goals through engineering tasks. These findings validate the model’s capacity to enhance both cognitive and civic learning outcomes in technical education. This research offers a pedagogical model that bridges vocational skill mastery and national character formation. It contributes to the discourse on contextual and identity-based education by offering an empirically tested approach adaptable to similar educational and cultural settings.